Multi-stress tolerant plant growth promoting Pseudomonas spp. MCC 3145 producing cytostatic and fungicidal pigment. (April 2017) - Patil, Sandeep; Nikam, Monali; Anokhina, Tatyana; Kochetkov, Vladimir; Chaudhari, Ambalal
Abstract: The plant growth promoting bacterial strain 213B was isolated from rice rhizosphere and identified with phenetic, fatty acid profiling, 16 S ribotyping (NCBI accession no. KF291253) and phylogenetic tree as Pseudomonas spp. The strain demonstrated multiple plant growth promoting traits including phosphate solubilization production of indole-3-acetic acid (IAA), hydrogen cyanide (HCN), ammonia and secreted different bioactive metabolites including phenazine, biosurfactant and siderophore. Mung bean ( Vigna radiata ) seed coated with the strain had shown enhanced seed germination and plant root length. Besides, the strain exhibited significant tolerance against common agricultural contaminants like salt, metals, herbicide and pesticides. Of the bioactives, strain was able to produce yellow colored phenazine derivatives in Pigment Production Medium D (PPMD) after 96 h at 28 ℃ and 120 rpm. The yellow compound was extracted and purified to obtain needle crystals and further characterized by HPLC, FTIR, LCMS, 1 H and 13 C NMR, EDAX and XRD analysis as phenazine-1-carboxylic acid (PCA). The purified PCA showed profound fungicidal activity against major phytopathogens including Colletotrichum circinans, Colletotrichum dematium, Fusarium oxysporum, Rhizoctonia solani and Sclerotinia sclerotiorum, while, substantial cytostatic activity (<10 μg ml -1 ) against breast (MCF-7), lung (A549), cervical (HeLa) and liver (Hep-G2) cancer cell lines in dose dependent manner. Thus, the present study unraveled the innate plant growth promoting Pseudomonas spp. MCC 3145 with biotic and abiotic stress tolerant attributes. Besides, the organism was able to produce PCA having fungicidal and cytostatic competency for therapeutic use and for sustainable crop production. Highlights: Salt, pesticide and metal resistant Pseudomonas spp. MCC 3145 with multiple plant growth promoting traits. Phenazine-1-carboxylic acid from multi-stress resistant Pseudomonas spp. MCC 3145. Phenazine-1-carboxylic acid was explored as (i) fungicidal agent against several phytopathogens and (ii) cytostatic agent against four major cancer cell lines.